THE INFLUENCE OF CONSUMER TRUST AND BRAND IMAGE ON COMPETITIVE ADVANTAGE AND ITS IMPLICATIONS IN PURCHASE DECISION - Prayudi, Dicki; Oktaviani, Renny (Journal of Management Review, 2023)
Hotel is a type of tourism business that is always needed by tourists. Sukabumi is a tropical area that is always visited by local and national tourists. However, hotel sales in this region do not always reach peak positions. The purpose of this research is to examine what variables influence the decision to stay at a hotel. Four variables were tested, namely consumer trust, brand image, competitive advantage and purchasing decisions to calculate how much these variables are interconnected. The method uses SEM supported by SPSS and the MRA method. The results with the MRA (Moderated Regression Analysis) test obtained Consumer Trust at 8,101 and MRA II at 22,439 which have a positive effect on competitive advantage which has implications for purchasing decisions. This hotel research in Sukabumi has only been studied with four test variables.